Predictive Value of the Model of End-Stage Liver Disease in Cirrhotic Patients with and without Spontaneous Bacterial Peritonitis - Bledar Kraja; Marsela Sina; Iris Mone; Fatjona Pupuleku; Adriana Babameto; Skerdi Prifti; Genc Burazeri (Gastroenterology Research and Practice)
Objective. We aimed to assess the predictive value of the model of end-stage liver disease (MELD) in hospitalized cirrhotic patients with and without spontaneous bacterial peritonitis (SBP) and fatal outcome. Methods. A cross-sectional study included 256 consecutive patients (199 men and 57 women) diagnosed with cirrhosis and ascites who were hospitalized at the University Hospital Center in Tirana from January 2008 to December 2009. SBP was defined as a neutrophil count of ≥250 cells/mm3 in ascitic fluid. MELD score was based on laboratory parameters determined by UNOS Internet site MELD calculator. Results. In multivariable-adjusted logistic regression models controlling for age, sex, diabetes, and etiology, there was evidence of a positive association of SBP with MELD score: the odds ratio (OR) for SBP for one unit increment of MELD score was 1.06 (95% Cl = 1.021.09). MELD score was significantly higher in fatal cases than nonfatal patients (mean age-adjusted score was 32.7 versus 18.4 overall; 34.8 versus 18.0 in SBP patients, and 32.0 versus 18.5 in non-SBP patients; all P<0.001). Conclusions. In this Albanian sample of hospitalized cirrhotic patients, MELD score was confirmed as a significant predictor of both SBP and fatal outcome.